The demand for energy in Thailand - Preecha Eagkunagul; Clarke Harry R.; Oudheusden, Dirk L. Van; Tang, John C.S.; Despiegelaere, W.L.M.; The Government of the Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1981)
This research is a preliminary attempt to analyze the energy demand system in Thailand. The study focuses on the demand for petroleum products and electricity under the influence of prices and economic growth. In the first part, the past energy consumption, its relationship to economic growth and the general energy situation are surveyed . Then, an analysis of both aggregate and sectoral energy demand is carried out by using econometric methods to quantify the past behavior of energy demand. The results obtained show that oil and electricity are apparently complementary and price inelastic, with a higher response of electricity demand to economic growth. These characteristics vary over types of energy and depend highly on the purpose for which the energy is used. Finally, the energy demand is projected to the future by using the estimated demand models to forecast the pattern and growth rates of oil and electricity demand in the next decade. With supplementary data on indigenous energy sources utilization, the total petroleum requirement is subsequently determined and it is concluded that the development of indigenous energy sources would reduce considerably the dependence of Thailand on imported petroleum.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Energy consumption -- Thailand